Electronic device, case, and glass product
By using the number of atoms of carbon and silicon elements on glass products accounted for more than 50 % of the coating layer, combined with the transparent and hard layer and optical coating layer, it solves the problem of insufficient resistance to glass surface and abrasion capacity in existing technologies. , Achieve higher hardness and service life.
Patent Information
- Application Number
- CN202310899707.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-07-20
- Publication Date
- 2025-01-21
AI Technical Summary
In the prior art, the scratch resistance and wear resistance of the glass surface cannot meet the higher requirements of users, and the thickness and hardness of the diamond-like (DLC) layer are unstable, affecting the service life of the glass.
A coating layer containing more than 50% of the atoms of carbon and silicon elements is used as a super-hard protective layer for glass products, including a transparent hard layer and an optical coating layer. Materials such as carbon-silicon bonds are deposited through a sputtering coating process to improve the surface of the glass. of hardness and scratch resistance.
It significantly improves the scratch and abrasion resistance of the glass surface to meet higher usage requirements, and keeps the light absorption in the visible light band small to avoid affecting the amount of light entering the lens.
Smart Images

Figure CN119330609A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of appearance structural parts of electronic equipment, and in particular to an electronic equipment, a housing and a glass product. Background Art
[0002] Glass is a common material on the surface of electronic products such as mobile phones. Glass is colorless and has a single-sided reflectivity of about 4%. In order to make the glass have anti-reflection (reduce reflectivity), brightening (increase reflectivity) and various color effects, a common method is to coat the surface of the glass with a nano-optical thin film coating of a certain thickness (usually several hundred nanometers). The optical coating can give the glass the above effects through optical interference.
[0003] Chemically strengthened glass generally has a surface hardness of about 8Gpa. By depositing a certain thickness of high-hardness thin film coating on the glass surface, the above-mentioned transmittance enhancement, brightness enhancement and various color optical effects can be achieved while improving the scratch and wear resistance of the glass surface. However, the hardness of the thin film coating in conventional technical solutions cannot meet the higher requirements of users for the surface hardness of electronic products. Summary of the invention
[0004] In a first aspect, an embodiment of the present application provides a glass product, wherein the glass product comprises:
[0005] substrate;
[0006] A transparent hardening layer is provided on the substrate;
[0007] Among them, the transparent hardened layer includes main elements and auxiliary elements; the main elements include carbon and silicon, and the auxiliary elements include any one or more of aluminum, titanium, zirconium, oxygen, nitrogen, and hydrogen; the atomic number of the main element accounts for more than 50%.
[0008] In a second aspect, an embodiment of the present application provides an electronic device, wherein the electronic device includes a display screen, and the glass product described in the above embodiment is provided on the display screen.
[0009] In a third aspect, an embodiment of the present application provides a shell, which is used to protect a device, and the shell includes the glass product described in the above embodiment.
[0010] The glass product provided in the embodiment of the present application can greatly improve the scratch resistance and wear resistance of the substrate by using a coating layer in which the atomic number of carbon and silicon elements accounts for more than 50% as the super-hard protective layer of the shell. BRIEF DESCRIPTION OF THE DRAWINGS
[0011] In order to more clearly illustrate the technical solutions in the embodiments of the present application, the drawings required for use in the description of the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present application. For ordinary technicians in this field, other drawings can be obtained based on these drawings without creative work.
[0012] Figure 1 It is a schematic diagram of the stacked structure of a conventional technical solution for a mobile phone housing;
[0013] Figure 2 is a schematic diagram of a stacked structure of an embodiment of the glass product of the present application;
[0014] Figure 3 is a schematic diagram of a stacked structure of another embodiment of the glass product of the present application;
[0015] Figure 4 is a schematic diagram of a stacked structure of another embodiment of the glass product of the present application;
[0016] Figure 5 is a schematic diagram of a stacked structure of another embodiment of the glass product of the present application;
[0017] Figure 6 is a schematic diagram of a stacked structure of another embodiment of the glass product of the present application;
[0018] Figure 7 is a schematic diagram of a structural scheme of a glass product used as a display screen cover in an embodiment of the present application;
[0019] Figure 8 is a schematic diagram of the cross-sectional structure of an embodiment of the electronic device of the present application;
[0020] Fig. 9 This is a schematic diagram of a stacked structure of an embodiment of the glass product of the present application when used as a shell;
[0021] Fig.10 It is a schematic diagram of the structural composition block diagram of an embodiment of the electronic device of the present application. DETAILED DESCRIPTION
[0022] The present application is further described in detail below in conjunction with the accompanying drawings and examples. It is particularly noted that the following examples are only used to illustrate the present application, but are not intended to limit the scope of the present application. Similarly, the following examples are only some embodiments of the present application rather than all embodiments, and all other embodiments obtained by ordinary technicians in the field without making creative work are within the scope of protection of the present application.
[0023] The terms "first", "second", and "third" in the embodiments of the present application are only used for descriptive purposes, and cannot be understood as indicating or implying relative importance or implicitly indicating the number of indicated technical features. Thus, the features defined as "first", "second", and "third" can expressly or implicitly include at least one of the features. In the description of the present application, the meaning of "multiple" is at least two, such as two, three, etc., unless otherwise clearly and specifically defined. In the embodiments of the present application, all directional indications (such as up, down, left, right, front, back...) are only used to explain the relative position relationship, movement, etc. between the components under a certain specific posture (as shown in the accompanying drawings). If the specific posture changes, the directional indication also changes accordingly. The terms "including" and "having" in the embodiments of the present application and any of their variations are intended to cover non-exclusive inclusions. For example, a process, method, system, product, or device that includes a series of steps or units is not limited to the listed steps or units, but optionally also includes steps or units that are not listed, or optionally also includes other steps or components inherent to these processes, methods, products, or devices.
[0024] Reference to "embodiments" herein means that a particular feature, structure, or characteristic described in conjunction with the embodiments may be included in at least one embodiment of the present application. The appearance of the phrase in various locations in the specification does not necessarily refer to the same embodiment, nor is it an independent or alternative embodiment that is mutually exclusive with other embodiments. It is explicitly and implicitly understood by those skilled in the art that the embodiments described herein may be combined with other embodiments.
[0025] As used herein, "electronic devices" (or simply "terminals") include, but are not limited to, devices configured to receive / send communication signals via a wireline connection (e.g., via a public switched telephone network (PSTN), a digital subscriber line (DSL), a digital cable, a direct cable connection, and / or another data connection / network) and / or via a wireless interface (e.g., for a cellular network, a wireless local area network (WLAN), a digital television network such as a DVB-H network, a satellite network, an AM-FM broadcast transmitter, and / or another communication terminal). Communication terminals configured to communicate via a wireless interface may be referred to as "wireless communication terminals", "wireless terminals" or "mobile terminals". Examples of mobile terminals include, but are not limited to, satellite or cellular phones; personal communication system (PCS) terminals that may combine cellular radiotelephones with data processing, fax, and data communication capabilities; PDAs that may include radiotelephones, pagers, Internet / intranet access, web browsers, organizers, calendars, and / or global positioning system (GPS) receivers; and conventional laptop and / or palmtop receivers or other electronic devices that include radiotelephone transceivers. A mobile phone is an electronic device equipped with a cellular communication module.
[0026] See also Figure 1 , Figure 1 This is a schematic diagram of the stacked structure of a conventional technical solution for a mobile phone housing. The prior art adopts Figure 1 In the stacked structure, the back side (non-user contact side) of the glass substrate 10a is first covered with a color ink layer 10b, and then a silicon nitride transparent hardening layer 10c, a sputter-deposited diamond-like carbon (DLC) layer 10d and an anti-fingerprint (AF) layer 10e are sequentially sputter-coated on the outer surface (user contact side) of the glass substrate 10a.
[0027] Among them, the silicon nitride transparent hardened layer 10c is mainly composed of two nano-films of silicon nitride and silicon oxynitride alternately stacked. The hardness of the two is greater than 15Gpa, which is much higher than the hardness of the glass surface. Therefore, it can improve the scratch and wear resistance of the glass surface; the thickness of the DLC layer 10d is about 3nm~5nm, and the hardness of the sputtering deposited DLC layer 10d is generally 5Gpa~20Gpa, which can further improve the surface hardness of the glass; the AF anti-fingerprint layer 10e is 20nm~30nm thick, attached to the DLC layer 10d, in direct contact with the user's use environment, providing the glass with anti-fingerprint and anti-fouling capabilities.
[0028] The main disadvantages of the above technical solution are: (1) The diamond-like carbon (DLC) layer in the prior art is deposited using a magnetron sputtering process. The thickness of the diamond-like carbon (DLC) layer is generally 3-15 nanometers. Due to its thin thickness, the hardness of the diamond-like carbon (DLC) layer of this thickness is generally 5Gpa~20Gpa. Its hardness is not stable and is greatly affected by factors such as coating temperature and residual gas. The improvement of the glass's scratch resistance is limited; (2) Diamond-like carbon (DLC) material is a visible light absorbing material. The cameras under the panels of mobile phones, Pads, etc. have strict requirements on the amount of visible light entering. The light absorption of DLC materials will affect the image effect; (3). The surface roughness of the coating of the existing solution is high. The outermost anti-fingerprint layer is a soft organic material. The anti-fingerprint layer is more easily punctured and worn when it comes into contact with hard objects. The steel wool friction test can generally only meet the test results of 3,000 frictions, and cannot meet the current requirement of 10,000 test results.
[0029] Based on the above problems, the present application provides a glass product for electronic devices. The glass product can be used as a transparent cover of an electronic device display screen or as a back cover of an electronic device, etc., which is not specifically limited here. Figure 2 , Figure 21 is a schematic diagram of a laminated structure of an embodiment of a glass product of the present application. It should be noted that the electronic device in the present application may include a mobile phone, a tablet computer, a laptop computer, a wearable device, and other electronic devices with a housing. The glass product 10 includes but is not limited to the following structures: a substrate 100, an optical coating layer 200, and a transparent hardening layer 300.
[0030] Specifically, the optical coating layer 200 is plated on one side surface of the substrate 100. It should be noted here that the substrate 100 in the embodiment of the present application can be conventional silica glass, or other glass, which is not specifically limited here. The substrate 100 can be glass with a smooth surface, or it can be a frosted glass with an etched surface. On the one hand, the surface of the etched glass is rough, and the surface reflected light is mainly scattered, which can play an anti-glare effect. Common processing methods for etched glass include mechanical sandblasting etching, chemical reaction etching, high-energy particle bombardment etching, etc. The substrate 100 in this scheme can use surface etched glass instead of smooth glass, and the optical coating layer 200 on the outer surface can be arranged on the etched surface of the glass. The optical coating layer 200 is arranged on the outer surface of the etched glass substrate. In addition to the above advantages, the uneven surface of the etched glass, when worn, the contact point is the convex position of the glass surface, and the position of the pit can be protected, so the wear and scratches on the surface are discontinuous, which can further improve the wear and scratch resistance of the glass surface. The thickness of the substrate 100 is greater than or equal to 0.05 mm and less than or equal to 3.0 mm, and the description here is mainly based on glass.
[0031] Optionally, the transparent hard layer 300 is disposed on the optical coating layer 200. The transparent hard layer 300 includes a main element and an auxiliary element; wherein the main element includes carbon and silicon, and the auxiliary element includes any one or more of aluminum, titanium, zirconium, oxygen, nitrogen, and hydrogen; the number of atoms of the main element accounts for more than 50%. The thickness of the transparent hard layer 300 ranges from 1nm to 200nm, and can be specifically 1nm, 3nm, 5nm, 10nm, 50nm, 100nm, 120nm, 150nm, and 200nm, etc.
[0032] The transparent hardened layer 300 is deposited using a sputtering coating process. One or more carbon-silicon bonds (C-Si), carbon-nitrogen bonds (CN), carbon sp3 hybrid bonds, and carbon sp2 hybrid bonds can be measured in the material of this layer, which can significantly improve the surface hardness and scratch resistance of the coated substrate. The atomic ratio of carbon and silicon elements in the surface hardened layer has a significant effect on the surface hardness and scratch resistance of the panel product. Take the measured data of the surface hardened layer deposited under two different process conditions as an example:
[0033] Embodiment 1 of the present application: The measured atomic number ratio in the surface hardening layer is Si 32 C 41 N8 O 19 For panel products (elements with a quantity ratio of less than 1% are not listed), a Mohs hardness pen was used for surface scratch testing. The pen tip with a Mohs hardness of 7 was loaded with 1000g. No obvious scratches were seen under indoor lighting, and visible scratches began to appear when the load was increased to 1300g. Using 120-grit quartz sandpaper for friction, with a load weight of 1000g, a 1mm*1mm grinding head, and a stroke of 40mm~60mm, no obvious scratches were seen after 200 reciprocating frictions, and visible scratches began to appear after 300 reciprocating frictions.
[0034] As a comparative example 1: the measured atomic number ratio of the surface hardening layer is Si 28 C 20 N 11 O 41 For panel products (elements with a quantity ratio of less than 1% are not listed), a Mohs hardness pen is used for surface scratch testing. The pen tip has a Mohs hardness of 6. When the load weight is greater than or equal to 500g, visible scratches are observed under indoor lighting. When rubbed with 120-grit quartz sandpaper, a load weight of 1000g, a 1mm*1mm grinding head, a stroke of 40mm-60mm, and friction of greater than or equal to 100 back and forth strokes, visible scratches begin to appear.
[0035] As comparative example 2: the measured atomic number ratio of the surface hardening layer is Si 18 C 20 N 21 O 41 For panel products (elements with a quantity ratio of less than 1% are not listed), a Mohs hardness pen is used for surface scratch testing. The pen tip has a Mohs hardness of 6. When the load weight is greater than or equal to 300g, visible scratches are observed under indoor lighting. When rubbed with 120-grit quartz sandpaper, a load weight of 1000g, a 1mm*1mm grinding head, a stroke of 40mm-60mm, and friction of greater than or equal to 50 back and forth, visible scratches begin to appear.
[0036] As comparative example 3: the measured atomic number ratio of the surface hardening layer is Si 20 C 10 N 21 O 49 For panel products (elements with a quantity ratio of less than 1% are not listed), a Mohs hardness pen is used for surface scratch testing. The pen tip has a Mohs hardness of 6. When the load weight is greater than or equal to 200g, visible scratches are observed under indoor lighting. When rubbed with 120-grit quartz sandpaper, a load weight of 1000g, a 1mm*1mm grinding head, a stroke of 40mm-60mm, and friction of greater than or equal to 20 back and forth, visible scratches begin to appear.
[0037] After multiple sets of experimental tests and comparisons, in order to ensure the scratch resistance of the product surface, the number of atoms of carbon and silicon elements in the surface hardened layer must account for more than 50% to achieve the anti-scratch effect under preset conditions.
[0038] Optionally, the structure of the optical coating layer 200 is generally formed by alternating the superposition of materials with different refractive indices according to the results of optical software simulation. The materials used can be any two or more of silicon nitride, silicon oxynitride, silicon oxide, silicon aluminum oxide, silicon aluminum nitride, silicon aluminum oxynitride, aluminum oxide, aluminum nitride, aluminum oxynitride, titanium nitride, titanium oxide, zirconium oxide, and zirconium nitride. The main function of the optical coating layer is to reduce or increase the light reflectivity of the surface of the coated substrate. If a large proportion of nitrides or oxynitrides with higher hardness are selected, the scratch resistance and wear resistance of the substrate on the user contact surface can be significantly improved. The thickness of the optical coating layer 200 is generally greater than 100nm and less than 3000nm. The total thickness of nitrides and oxynitrides in the optical coating layer accounts for more than 50%.
[0039] Optionally, the optical coating layer 200 and the transparent hardened layer 300 in the embodiment of the present application have an average refractive index of the coating material greater than or equal to 1.67. For the nitrides and nitride oxides selected in the optical coating layer 200, a higher average refractive index will bring higher surface hardness and better scratch resistance.
[0040] Among them, the optical coating layer 200 and the transparent hardened layer 300 are cut into 2nm thick materials at any position in the direction perpendicular to the user contact surface. The upper and lower surfaces of the 2nm thin layer are named surface A and surface B. Then the absolute value of the difference in the refractive index of the materials between the two surfaces A and B is less than or equal to 2.0. Minimizing the refractive index difference between the two surfaces A and B can weaken the interface effect and enhance the adhesion and wear resistance of the coating layer.
[0041] The residual stress of the coating layer (including the optical coating layer 200 and the transparent hardened layer 300) is calculated based on the contour change of the substrate before and after coating, and a residual stress greater than or equal to 400Mpa can be measured. A greater stress means that the coating layer has a higher density and a smaller porosity, which can improve the hardness and scratch resistance.
[0042] The glass product with an ultra-hard surface in the embodiment of the present application can change its surface reflectivity or transmittance according to actual needs after being covered with a coating layer, and its optical characteristics in the 380nm-800nm band meet one of the following characteristics: (1) The single-sided average reflectivity of the user contact surface is greater than or equal to 0.3% and less than or equal to 5.0%. Reducing the reflectivity can reduce surface glare and improve the visual comfort of the user when viewing; (2) The single-sided average reflectivity of the user contact surface is greater than 5% and less than 60%. Although increasing the reflectivity will cause glare and reduce visual comfort when viewing in a strong light environment, it can present richer colors in a weak light environment, such as indoors, and increase the appearance expression.
[0043] The glass product with a superhard surface in the embodiment of the present application satisfies the condition that the single-side average reflectivity of the user contact surface in the band of 380nm to 800nm is greater than or equal to 0.3% and less than or equal to 5%. In the (L*, a*, b*) colorimetric system, a D65 light source is used, the incident light angle is 5° or 10°, and the square root of the reflectivity color values a* and b* of the user contact surface is less than or equal to 6, that is, The smaller the square root of the reflectance color values a* and b*, the closer the surface color of the product is to colorless.
[0044] The glass product with an ultra-hard surface in the embodiment of the present application has a small color difference when observed at a large angle, when the average single-side reflectivity of the user contact surface in the 380nm-800nm band is greater than or equal to 0.3% and less than or equal to 5%. That is, when a D65 light source is used and the incident light angle is 45°, in the (L*, a*, b*) colorimetric system, the square roots of the reflectivity color values a* and b* of the user contact surface also meet the requirement of being less than or equal to 6, that is,
[0045] The glass product with an ultra-hard surface in the embodiment of the present application is subjected to a surface scratch test using a Mohs hardness pen from a position perpendicular to the user contact surface. When observed under indoor lighting, it can be measured that the surface Mohs hardness is greater than 7 and no obvious scratches will occur when the load weight is greater than or equal to 1000g. The surface Mohs hardness of the uncoated tempered glass is 6 and visible scratches will occur when the load weight is greater than or equal to 500g. The surface resistance to scratches by sharp objects is significantly improved after coating.
[0046] The glass product with an ultra-hard surface in the embodiment of the present application is tested for surface hardness using a Berkovich indenter perpendicular to the user contact surface, with a test depth greater than 100 nm or a test load equal to 5 mmN. The measurable surface hardness is greater than 13 GPa and the elastic modulus is greater than 120 GPa. The surface hardness of the uncoated tempered glass is about 8 GPa and the elastic modulus is about 80 GPa. After coating, the surface hardness and elastic modulus are increased by more than 50%.
[0047] The glass products with super-hard surfaces in the embodiments of the present application are subjected to a sandpaper friction test perpendicular to the user surface, using 120-grit quartz sandpaper, a load weight of 1000g, a 1mm*1mm grinding head, a stroke of 40mm to 60mm, and no obvious scratches will appear after 200 reciprocating frictions. However, the tempered glass surface without hard coating will show visible scratches after 50 reciprocating frictions.
[0048] The glass product with an ultra-hard surface in the embodiment of the present application is subjected to a vibration friction test using a Rosler vibration friction tester. The vibration test lasts for more than 1.0 hour, and no obvious wear and tear occurs on the user contact surface.
[0049] The glass product with an ultra-hard surface in the embodiment of the present application is tested for surface roughness using an atomic force microscope, and the Ra roughness of the user contact surface is less than 10 nm. Lower surface roughness can increase user tactile comfort and improve surface wear resistance.
[0050] See also Figure 3 , Figure 3 It is a schematic diagram of the stacked structure of another embodiment of the glass product of the present application. Different from the aforementioned embodiment, the glass product 10 in this embodiment includes the following structures: a substrate 100, an optical coating layer 200, a transparent hard layer 300 and an anti-fingerprint layer 400. Among them, the optical coating layer 200 is coated on one side surface of the substrate 100. The transparent hard layer 300 is arranged on the optical coating layer 200. The formation method of the transparent hard layer 300 and the optical coating layer 200 can refer to the relevant description of the aforementioned embodiment, which will not be repeated here. The anti-fingerprint layer 400 is arranged on the transparent hard layer 300. The specific formation method of the anti-fingerprint layer 400 can be evaporation or sputtering, and the anti-fingerprint layer 400 is used to enhance the anti-fingerprint and anti-fouling capabilities of the glass surface.
[0051] See also Figure 4 , Figure 4 1 is a schematic diagram of a laminated structure of another embodiment of the glass product of the present application. The glass product 10 in this embodiment also includes the following structures: a substrate 100, an optical coating layer 200, a transparent hard layer 300 and an anti-fingerprint layer 400. The optical coating layer 200 is plated on one side of the substrate 100, the transparent hard layer 300 is disposed on the optical coating layer 200, and the anti-fingerprint layer 400 is disposed on the transparent hard layer 300.
[0052] Optionally, the optical coating layer 200 in this embodiment includes alternating superimposed layers of silicon nitride 210 and silicon oxynitride 220 materials. In some other embodiments, it may also be composed of only two nanomaterial layers of silicon dioxide and silicon nitride alternatingly superimposed. Silicon dioxide is relatively soft (its hardness is equivalent to that of glass), but its refractive index is low, and the difference between its refractive index and that of silicon nitride is large, so it is easier to choose silicon dioxide for optical interference to form a highly saturated reflective color. There is no limit to the total number of layers of silicon nitride 210 and silicon oxynitride 220 of the optical coating layer 200, and the total thickness is generally between 100nm and 3000nm, and can specifically be 100nm, 200nm, 500nm, 1000nm, 2000nm, 3000nm, etc.
[0053] See also Figure 5 , Figure 5 1 is a schematic diagram of a laminated structure of another embodiment of the glass product of the present application. The glass product 10 in this embodiment also includes the following structures: a substrate 100, an optical coating layer 200, a transparent hard layer 300, and an anti-fingerprint layer 400. The detailed structural features of the substrate 100, the optical coating layer 200, the transparent hard layer 300, and the anti-fingerprint layer 400 can be found in the relevant description of the aforementioned embodiment, and will not be repeated here.
[0054] Different from the above-mentioned embodiment, the glass product in this embodiment further includes a first connecting layer 500 and a second connecting layer 600, wherein the first connecting layer 500 may be disposed between the optical coating layer 200 and the substrate 100, and the second connecting layer 600 may be disposed between the optical coating layer 200 and the transparent hardened layer 300. The materials of the first connecting layer 500 and the second connecting layer 600 may be selected from any one or more of silicon oxide, aluminum oxide, silicon aluminum oxide, zirconium oxide, silicon oxynitride, and aluminum oxynitride. In one embodiment, the first connecting layer 500 may be connected to the substrate 100 using silicon dioxide material to improve the connection strength between the optical coating layer 200 and the substrate 100 as a whole. Similarly, the second connecting layer 600 may also be made of silicon dioxide material to increase the connection strength between the optical coating layer 200 and the transparent hardened layer 300. The thickness of the first connecting layer 500 and the second connecting layer 600 may both be in the range of 2 nm to 300 nm. The material composition of the first connecting layer 500 and the second connecting layer 600 is close to that of the substrate 100, which can maximize the adhesion between the coating layer and the substrate.
[0055] The present application embodiment takes a glass product with 0.5 mm tempered glass as a substrate as an example, and the detailed implementation is as follows.
[0056] (1) Use the chemically strengthened cover glass (substrate 100), thoroughly clean and dry the surface, put it into the coating equipment, and evacuate it to a pressure below 0.001 Pa;
[0057] (2) Use plasma to clean the glass surface to improve surface activity, and the cleaning time is 1min to 10min;
[0058] (3) Sputtering deposition of silicon dioxide (first connection layer 500), coating thickness 10nm;
[0059] (4) Sputtering deposition of silicon oxynitride (material layer) 220, coating thickness 78.7nm;
[0060] (5) Sputtering deposition of silicon nitride (material layer) 210, coating thickness 75.5nm;
[0061] (6) Sputtering deposition of silicon oxynitride, coating thickness 11.8nm;
[0062] (7). Sputtering deposition of silicon nitride, coating thickness 35.2nm;
[0063] (8). Sputtering deposition of silicon oxynitride, coating thickness 87.9nm;
[0064] (9). Sputtering deposition of silicon nitride, coating thickness 25.9nm;
[0065] (10). Sputtering deposition of silicon oxynitride, coating thickness 22.4nm;
[0066] (11). Sputtering deposition of silicon nitride, coating thickness 71.6nm;
[0067] (12) Sputtering deposited silicon dioxide (second connection layer 600), coating thickness 88.3nm;
[0068] (13) Sputtering deposition of transparent hardened layer 300, coating thickness 1nm ~ 200nm;
[0069] (14) Depositing an anti-fingerprint layer 400, first depositing 5nm to 10nm silicon oxide, and then depositing a perfluoropolyether organic substance, with a total thickness of 10nm to 30nm;
[0070] (15) Other subsequent processing steps.
[0071] The above steps are merely a parameter implementation example, and those skilled in the art can adjust and design the above parameters according to actual needs.
[0072] The glass products in the embodiments of the present application can greatly improve the scratch resistance and wear resistance of the substrate by using a coating layer in which the atomic number of carbon and silicon elements accounts for more than 50% as the super-hard protective layer of the glass products; wherein, the transparent hardened layer has the characteristic of low light absorption in the visible light band, and the transparent hardened layer is deposited on the front cover glass of the electronic device without affecting the amount of light entering the lens; in addition, the surface roughness of the transparent hardened layer is low, which is conducive to improving the service life of the anti-fingerprint layer on its outer surface. In addition, by setting a first connecting layer between the optical coating layer and the substrate and setting a second connecting layer between the optical coating layer and the transparent hardened layer, the connection strength between adjacent layers can be increased, thereby improving the reliability of the laminated structure of the glass products.
[0073] See also Figure 6 , Figure 6 1 is a schematic diagram of the stacked structure of another embodiment of the glass product of the present application. The glass product 10 in this embodiment includes the following structures: a substrate 100, a third connecting layer 101, a transparent hardening layer 300 and an anti-fingerprint layer 400. Different from the previous embodiment, the glass product in this embodiment may not include an optical coating layer, but only strengthens the surface of the substrate. The substrate 100 may be made of a material with color or texture effects. The detailed technical features of this part are within the scope of understanding of those skilled in the art and will not be repeated here.
[0074] In addition, the present application also provides a solution in which a glass product is used as a display screen cover. Figure 7 , Figure 7 It is a schematic diagram of the structural scheme of the glass product in the embodiment of the present application as a display screen cover, wherein the glass product 10 is covered on the light-emitting surface of the display screen 30, and the structural assembly (the structure of the glass product 10 and the display screen 30) can be used in electronic devices.
[0075] Furthermore, the present application also provides an electronic device, see Figure 8 , Figure 8 1 is a schematic diagram of a cross-sectional structure of an embodiment of an electronic device of the present application. In this embodiment, the glass product 10 is used as a housing of the electronic device, i.e., a battery cover. The electronic device in this embodiment may include a display screen 30, a glass product 10, and a control circuit board 20. The structure of the glass product 10 (battery cover, i.e., rear cover) may be as described in the above embodiments.
[0076] Also, see Fig. 9 , Fig. 91 is a schematic diagram of a laminated structure of an embodiment of the glass product of the present application when used as a housing. Different from the above-mentioned embodiment, the glass product 10 in this embodiment further includes a color development layer 700, a second optical coating layer 800 and a primer layer 900. The color development layer 700 is disposed on the side of the substrate 100 away from the optical coating layer 200.
[0077] Specifically, the primer layer 900 can be an organic material, generally a resin material or an organosilicon compound material, such as modified polyurethane, polysiloxane, etc. The material of the primer layer 900 has a molecular structure that can be reliably connected to the second optical coating layer 800 and the substrate 100. The second optical coating layer 800 is arranged between the color development layer 700 and the primer layer 900. The glass product is sequentially composed of the color development layer 700, the second optical coating layer 800, the primer layer 900, the glass substrate 100, the first connecting layer 500, the optical coating layer 200, the second connecting layer 600, the transparent hardening layer 300 and the anti-fingerprint layer 400 from the inside to the outside. Among them, the second optical coating layer 800 can include any one of SiO2, TiO2, Nb2O5, Si3N4, Ta2O5, La2Ti2O7, ZrO2, Al2O3 nano-film material layers or a mixed superposition layer of multiple types. The glass product in this embodiment has more diverse color changes by providing the second optical coating layer and the color development layer.
[0078] Optionally, the color layer 700 can be sprayed with ink or a film film can be attached. The most commonly used colors of ink are black and white, but other colors are also possible. Compared with ink, the film film can also provide the color of ink for the back of the glass, and the film film can also make the glass surface present various texture effects. The specific formation method of the color layer 700 can be to clean the non-coated surface of the substrate 100 (the surface on the side away from the optical coating layer 200), generally using plasma cleaning to improve the surface activity; then cover the non-coated surface with ink or attach a film film. By forming a color layer on the inside of the shell, different colors and texture effects of the shell can be achieved.
[0079] Please continue reading Figure 8 Optionally, the display screen 30 and the glass product 10 cooperate to form a receiving space 1000, the control circuit board 20 is disposed in the receiving space 1000, the control circuit board 20 is electrically connected to the display screen 30, and the control circuit board 20 is used to control the operation of the display screen 30. The detailed technical features of the other parts of the electronic device are within the scope of understanding of those skilled in the art and will not be repeated here.
[0080] See also Fig.10 , Fig.10It is a schematic diagram of the structural composition block diagram of an embodiment of an electronic device of the present application. The electronic device can be a mobile phone, a tablet computer, a laptop computer, a wearable device, etc. The diagram of this embodiment takes a mobile phone as an example. The structure of the electronic device may include an RF circuit 910, a memory 920, an input unit 930, a display unit 940 (which may be the display screen 30 in the aforementioned embodiment), a sensor 950, an audio circuit 960, a wifi module 970, a processor 980 (which may be the control circuit board 20 in the aforementioned embodiment) and a power supply 990, etc. Among them, the RF circuit 910, the memory 920, the input unit 930, the display unit 940, the sensor 950, the audio circuit 960 and the wifi module 970 are respectively connected to the processor 980; the power supply 990 is used to provide power to the entire electronic device 10.
[0081] Specifically, the RF circuit 910 is used to receive and send signals; the memory 920 is used to store data instruction information; the input unit 930 is used to input information, which may specifically include a touch panel 931 and other input devices 932 such as operation buttons; the display unit 940 may include a display panel 941, etc.; the sensor 950 includes an infrared sensor, a laser sensor, etc., for detecting user approach signals, distance signals, etc.; the speaker 961 and the microphone (or microphone) 962 are connected to the processor 980 through the audio circuit 960 for receiving and sending sound signals; the wifi module 970 is used to receive and transmit wifi signals, and the processor 980 is used to process data information of the electronic device. For the specific structural features of the electronic device, please refer to the relevant description of the above embodiment, which will not be described in detail here.
[0082] The electronic device in this embodiment has a shell (display cover or battery cover, etc.) which can greatly improve the scratch and wear resistance of the substrate by using a coating layer in which the number of carbon and silicon atoms accounts for more than 50% as an ultra-hard protective layer of the shell.
[0083] The above descriptions are only some embodiments of the present application, and do not limit the protection scope of the present application. Any equivalent device or equivalent process transformation made using the contents of the present application specification and drawings, or directly or indirectly used in other related technical fields, are also included in the patent protection scope of the present application.
Claims
1. A glass product, characterized in that: The glass product comprises: substrate; A transparent hardening layer is provided on the substrate; Among them, the transparent hardened layer includes main elements and auxiliary elements; the main elements include carbon and silicon, and the auxiliary elements include any one or more of aluminum, titanium, zirconium, oxygen, nitrogen, and hydrogen; the atomic number of the main element accounts for more than 50%.
2. The glass product according to claim 1, characterized in that The auxiliary elements include oxygen and nitrogen.
3. The glass product according to claim 1, characterized in that: The molecular formula of the transparent hard layer is Si 32 C 41 N8O 19 .
4. The glass product according to claim 1, characterized in that The thickness of the transparent hardening layer ranges from 1 nm to 200 nm.
5. The glass product according to claim 1, characterized in that: The glass product further comprises an optical coating layer, and the optical coating layer is arranged between the transparent hardening layer and the substrate.
6. The glass product according to claim 5, characterized in that The optical coating layer includes alternating superimposed layers of any two or more materials selected from silicon nitride, silicon oxynitride, silicon oxide, silicon aluminum oxide, silicon aluminum nitride, silicon aluminum oxynitride, aluminum oxide, aluminum nitride, aluminum oxynitride, titanium nitride, titanium oxide, zirconium oxide, and zirconium nitride.
7. The glass product according to claim 6, characterized in that The optical coating layer includes alternating stacked layers of silicon nitride and silicon oxynitride materials.
8. The glass product according to claim 5, characterized in that The thickness of the optical coating layer ranges from 100 nm to 3000 nm.
9. The glass product according to claim 5, characterized in that: The average refractive index of the optical coating layer and the transparent hardened layer is greater than or equal to 1.
67.
10. The glass product according to claim 5, characterized in that The optical coating layer and the transparent hardened layer are cut into a 2nm thick material layer at any position in the direction perpendicular to the user contact surface. The upper and lower surfaces of the material layer are named surface A and surface B. Then the absolute value of the difference in material refractive index between the two surfaces A and B is less than or equal to 2.
0.
11. The glass product according to claim 5, characterized in that After the optical coating layer and the transparent hardened layer are formed, the residual stress of the glass product is greater than or equal to 400 MPa.
12. The glass product according to claim 5, characterized in that The optical characteristics of the glass product in the 380nm-800nm band meet the following requirements: the single-side average reflectivity of the user contact surface is greater than or equal to 0.3% and less than or equal to 5.0%, or the single-side average reflectivity of the user contact surface is greater than 5% and less than 60%.
13. The glass product according to claim 12, characterized in that When the optical characteristics of the glass product in the 380nm to 800nm band meet the requirement that the single-side average reflectivity of the user contact surface is greater than or equal to 0.3% and less than or equal to 5.0%, in the (L*, a*, b*) colorimetric system, using a D65 light source, the incident light angle is 5° or 10°, and the square roots of the reflectivity color values a* and b* of the user contact surface are less than or equal to 6, that is, When the incident light angle is 45°, the square roots of the reflectivity color values a* and b* of the user contact surface are also less than or equal to 6, that is, 14. The glass product according to claim 8, characterized in that The glass product further includes a first connecting layer, which is disposed between the optical coating layer and the substrate.
15. The glass product according to claim 14, characterized in that The glass product further includes a second connecting layer, which is arranged between the optical coating layer and the transparent hardening layer.
16. The glass product according to claim 15, characterized in that The material of the first connection layer and the second connection layer is selected from any one or more of silicon oxide, aluminum oxide, silicon aluminum oxide, zirconium oxide, silicon oxynitride, and aluminum oxynitride.
17. The glass product according to claim 16, characterized in that The thickness of the first connection layer and the second connection layer are both in the range of 2 nm to 300 nm.
18. The glass product according to claim 1, characterized in that The glass product further includes a third connecting layer, and the third connecting layer is arranged between the transparent hardening layer and the substrate.
19. An electronic device, comprising a display screen, characterized in that: The display screen is provided with the glass product as described in any one of claims 1-18.
20. A housing for protecting a device, characterized in that: The housing comprises the glass product according to any one of claims 1-18.
Citation Information
Cited By
High-hardness and scratch-resistant antireflection film and preparation method thereof
CN120006213A